The Position of Girls in Obstructing Brother's Inheritance: A Sunni and Shia Fiqh Perspective and the Supreme Court's Jurisprudence - Muhammady, Alfian; Kolopita, Abdul Fajri (Al-Mujtahid: Journal of Islamic Family Law, 2024)
This study aims to analyze the position of girls in hindering their brother's inheritance from the perspective of Sunni and Shia jurisprudence and the jurisprudence of the Indonesian Supreme Court. The research method used is a literature study with a descriptive-analytical approach, which involves the study of Sunni and Shia fiqh literature and the analysis of Supreme Court decisions related to inheritance cases. The results of the study show that there are significant differences between Sunni and Shia jurisprudence in determining the inheritance rights of girls. Sunni jurisprudence generally gives priority to boys, although girls still receive a share of the inheritance but do not completely block the rights of brothers. In contrast, Shia jurisprudence gives a stronger position to girls, which can reduce or hinder the inheritance rights of brothers. In the jurisprudence of the Supreme Court of Indonesia, efforts were found to harmonize the rules of fiqh with the principle of justice in national law, which aims to ensure a fairer distribution of inheritance. The conclusion of this study is that the interpretation of girls' inheritance law in the context of fiqh and national jurisprudence needs to be developed to achieve gender justice in the distribution of inheritance. The implication of this research is the importance of inheritance law reform that considers both fiqh perspectives and judicial decisions to create a fairer and more inclusive legal system in Indonesia.